Um estudo teórico-empírico sobre a comunicação interna e externa das instituições de ensino superior PUC/SP, UNIFAE E USCS: responsabilidade social, publicidade institucional e planejamento estratégico de comunicação - Biffi, Marcos Antonio (2021)
This research investigates the relationships between social responsibility, institutional advertising and strategic planning through the analysis of internal and external communication at higher education institutions PUC/SP, UNIFAE from São João da Boa Vista/SP and USCS from São Caetano do Sul/SP. The research problem sought to find out: to what extent is internal and external institutional dissemination capable of creating and communicating social, cultural and cognitive patterns that legitimize the organization of higher education in view of the community's wishes? The central objective was to reflect on the institutional communication actions in the higher education institutions mentioned as an active element of dissemination. To achieve this purpose, the research has a theoretical-empirical qualitative approach with the following theoretical axes: social responsibility, institutional communication and strategic communication planning. Field research was carried out through interviews with directors and managers of the aforementioned higher education institutions, with 45 structured and unstructured questions about internal and external communication, with a view to comparing, through the creation of categories, the institutional communication analyzed in order to apprehend the social, cognitive and cultural objectives that foster the 3 surveyed higher education institutions. The research results show that each higher education institution has distinct social, cultural and cognitive patterns that are a social construction inserted in a spirit of the time, being then transmitted, reinforced or even adapted through institutional advertising and strategic planning of internal and external communication. Next, 24 advertising images published by the researched higher education institutions in the period from 2017 to 2020 were analyzed. Finally, comparative analysis of the aforementioned higher education institutions were carried out, covering research and images. In general, the comparative results related to the research show that the higher education institutions have been presenting clear actions on the issue of social responsibility, but also difficulties in communicating what has been done, in view of the communication areas acting in order to meet specific and punctual demands without a communication plan